The Extension of the UTAUT2 Model: A Case Study of Indonesian SMEs Acceptance of Social Commerce - Arista, Artika; Tjahjanto, Tjahjanto; Ernawati, Iin; Purabaya, Rudhy Ho; Abdullah, Engku Fadzli Hasan Syed (Society of Visual Informatics, 2023)
An entirely updated e-commerce platform referred to as Social Commerce was developed in response to the rise in social media use. Social commerce integrates interactions between buyers and sellers made possible by social media platforms and Web 2.0 technology. It is frequently seen as a subfield of e-commerce. Social commerce has been successfully introduced in developing countries. Many businesses around the world are small and medium enterprises (SMEs). For instance, SMEs in Indonesia can contribute up to 60.34% of the country's GDP and have a substantial labor pool. Using social commerce as an e-commerce platform can significantly improve the operational efficiency of small and medium-sized enterprises (SMEs). However, little empirical research has specifically examined how SMEs embrace social commerce. Given the high level of concern, further research is required. Therefore, the current study experimentally examined how local SMEs in rural Indonesia introduced social commerce. The study was modeled using the Unified Theory of Technology Acceptance and Use (UTAUT) 2 model and several previous studies. SmartPLS 4 software was used to model and evaluate data using partial least squares structural equation modeling (PLS-SEM). The findings of the 114 samples showed that relative advantage, social support, facilitation conditions, and the government's support of social commerce influenced behavioral intention to use social commerce. Behavioral intention to use social commerce influences the actual use of social commerce. The findings of this study can help local governments and policymakers develop social trade promotion regulations to help potential SMEs and entrepreneurs gain long-term business support.